Comparison of preemptive kidney transplant recipients with nonpreemptive kidney recipients in single center: 5 years of follow-up - Sayin, Burak (Dove Medical Press, 2013)
BACKGROUND: For suitable patients with end-stage renal disease, kidney transplantation (KT) is the best renal replacement therapy, resulting in lower morbidity and mortality rates and improved quality of life. Preemptive kidney transplantation (PKT) is defined as transplantation performed before initiation of maintenance dialysis and reported to be associated with superior outcomes of graft and patient survival. In our study, we aimed to compare the 5-year outcomes of PKT and nonpreemptive kidney transplantation (NPKT) patients who received KT in our center, to define the differences according to complications, comorbidities, adverse effects, clinical symptoms, periodical laboratory parameters, rejection episodes, graft, and patient survival. METHODS: One hundred kidney transplantation (37 PKT, 63 NPKT) recipients were included in our study. All patients were evaluated for adverse effects, complications, comorbidities, clinical symptoms, monthly laboratory parameters, acute rejection episodes, graft, and patient survival. RESULTS: Acute rejection episodes were found to be significantly correlated with graft loss in both groups (P = 0.02 and P = 0.01, respectively). Hypertension after transplantation was diagnosed by ambulatory blood pressure measurement in 74 of 100 patients. Twenty-five of 37 (67.6%) of Group 1 (PKT) recipients had hypertension while 54 of 63 (85.4%) of Group 2 (NPKT) had hypertension. The incidence of hypertension between two groups was statistically significant (P = 0.03), but this finding was not correlated to graft survival (P = 0.07). Some patients had serious infections, requiring hospitalization, and were treated immediately. Infection rates between the two groups were 10.8% for Group 1 patients and 31.7% for Group 2 patients and were statistically significant (P = 0.02). Infection, requiring hospitalization, was found to be statistically correlated to graft loss in only NPKT patients (P = 0.00). CONCLUSION: While the comparison of PKT and graft and patient survival with NPKT is poorer than we expected, lower morbidity rates of hypertension and infection are similar with recent data. Avoidance of dialysis-associated comorbidities, diminished immune response, and cardiovascular complications are the main benefits of PKT.